Near-Infrared Spectroscopic Study of Chlorite Minerals. (26th February 2018) - Yang, Min; Ye, Meifang; Han, Haihui; Ren, Guangli; Han, Ling; Zhang, Zhuan
Abstract : The mineral chemistry of twenty chlorite samples from the United States Geological Survey (USGS) spectral library and two other regions, having a wide range of Fe and Mg contents and relatively constant Al and Si contents, was studied via infrared (IR) spectroscopy, near-infrared (NIR) spectroscopy, and X-ray fluorescence (XRF) analysis. Five absorption features of the twenty samples near 4525, 4440, 4361, 4270, and 4182 cm −1 were observed, and two diagnostic features at 4440 and 4280 cm −1 were recognized. Assignments of the two diagnostic features were made for two combination bands (ν + δ A l A l O − O H and ν + δ S i A l O − O H ) by regression with IR fundamental absorptions. Furthermore, the determinant factors of the NIR band position were found by comparing the band positions with relative components. The results showed that Fe/(Fe + Mg) values are negatively correlated with the two NIR combination bands. The findings provide an interpretation of the NIR band formation and demonstrate a simple way to use NIR spectroscopy to discriminate between chlorites with different components. More importantly, spectroscopic detection of mineral chemical variations in chlorites provides geologists with a tool with which to collect information on hydrothermal alteration zones from hyperspectral-resolution remote sensing data.